Beban Kerja dan Work Life Balance pada Kinerja Karyawan Generasi Millenial - Syaqiq, Muhammad; Nuromavita, Inka; Hakim, Mujibul (STKIP PGRI SITUBONDO, 2024)
This research aims to determine the effect of burnout and work life balance on the performance of millennial employees in Batang Regency. The respondents in this study were 87 millennial employees who were met randomly by researchers. The research approach uses quantitative descriptive analysis. The collected questionnaire data was processed using SPSS 22 software. The results of this research show that burnout has a positive and significant effect on performance. If employees do not experience burnout then their performance will be good. Work life balance has a significant positive effect on the performance of millennial employees in Batang Regency. Employees who can avoid burnout tend to be more productive and efficient in their work. Likewise, a good work life balance allows employees to work with more focus and motivation. Therefore, companies need to pay attention to these two aspects to maximize employee performance, especially the millennial generation, which increasingly dominates the workforce today.